Development of an Interactive E-Module Based on Project Based Learning (PjBL) Integrated with Pancasila Student Profile Strenghtening Project (P5) in Learning Plant Growth and Development - Jannah, Anindita Firdatul; Ridlo, Saiful; Marianti, Aditya; Dewi, Novi Ratna; Widiyatmoko, Arif (Journal of Biology Education, 2025)
The teaching materials in the current Merdeka Curriculum have not yet fully met students' needs. Based on a needs analysis, it was found that there is a demand for teaching materials that can integrate the Pancasila Student Profile Strengthening Project (P5) with the learning process. Initial observations also showed that students’ creativity and science process skills were at a low level. Therefore, this study developed an interactive e-module based on Project Based Learning (PjBL) integrated with P5 on the topic of plant growth and development. The purpose of this research was to examine the validity, readability, effectiveness, practicality, and describe the characteristics of the developed e-module. This research employed a Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The e-module was proven to be highly valid based on evaluations by content experts and media experts. The e-module demonstrates a high level of readability. The e-module was shown to be effective in enhancing students’ creativity and science process skills, as evidenced by cognitive and performance test results. Feedback from both teachers and students indicated that the e-module is highly practical for classroom use. Overall, the developed e-module has shown characteristics that integrate P5 activities on the topic of plant growth and development through project based learning.